O gestor brasileiro no exterior: e a academia, acompanha essas competências? - Sousa, Adriana de Faria e (2011)
The aim of this study was to identify how the syllabuses of undergraduate Brazilian Business Administration courses represented by a sample chosen among the courses that obtained grade 5 in ENADE (National Exam of Students Performance) and in MEC (Ministry of Education) evaluation contribute to the development of competencies that help preparing their students for the possibility of taking international assignments. It was taken account not only the expatriation processes, but also the voluntary search for new personal and professional challenges around the globe. It s a descriptive research, in which different methodologies were used for attaining the specific objectives proposed. A survey was conducted with Brazilian managers who work abroad in order to identify their main learning experiences, based on the studies of McCall and Hollenbeck (2003). Subsequently, the results were synthesized in groups People Management, Business Management, Stakeholders Management, Hierarchical Relationships, and Language and Culture which were related to the necessary competencies of a global manager, identified in the literature (ECHEVESTE et at. 1999). Thereafter, parameters have been proposed through which the course descriptions were evaluated, by means of classical content analysis, with word count made from the establishment of categories. In brief, we observed that about half the evaluated courses have indicators that the competencies were being developed among the students, being the most recurrent Strategic vision, followed by Decision-making Capacity. A total of 1324 course descriptions were evaluated, and in 622 of them it was possible to identify some kind of adherence to the 17 competencies proposed in this study. We came to the conclusion that Brazilian Business Administration courses seem to contemplate in their course descriptions the learning of the competencies that help capacitate a manager to work in an international context, but other personal and professional experiences must be added to them. Moreover, during the course, there is no direct relation with this scenario, except for a group of subjects that were evaluated under the category International Businesses. For future studies, we indicate an expansion of the survey to Brazilian professionals who work in different countries in order to eliminate possible biases. It is also possible to increase the number of surveyed universities and extend the analysis to interviewing returning students and teachers. We also indicate the necessity of a deeper study of educational projects and their relation with the contemporary labor market, in which there is a growing demand for professionals open to new personal and professional challenges.